Postępowanie egzekucyjne prowadzone przeciwko profesjonalnemu pełnomocnikowi będącym adwokatem a deontologia zawodu - Przybyszewski, Hubert (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Autor podejmuje się próby oceny naruszenia zasad deontologii zawodu adwokata w świetle wszczęcia i prowadzenia egzekucji przeciwko adwokatowi. Jednocześnie koncentruje się na identyfikacji i zachodzących relacji pomiędzy normami prawnymi, a normami deontologicznymi odnoszący się do wskazanego obszaru. Autor wykazuje również rolę samorządu w zakresie stanowienia norm deontologicznych oraz konsekwencji ich naruszenia.

The author attempts to assess the violation of the principles of the deontology of the profession of an advocate in the light of the initiation and conduct of enforcement against an attorney. At the same time, it focuses on the identification and relations between legal norms and deontological norms relating to the indicated area. The author also demonstrates the role of self-government in the establishment of deontological norms and the consequences of their violation.
Enforcement proceedings against a professional attorney who is a lawyer and the deontology of the profession
Keywords: adwokat; odpowiedzialność dyscyplinarna; samorząd zawodowy; etyka; advocate; disciplinary liability; professional self-government; ethics